ЗАКОНОДАТЕЛЬСТВО РЕСПУБЛИКИ КАЗАХСТАН О ВЕТЕРИНАРНОЙ БЕЗОПАСНОСТИ: ПРОБЛЕМЫ И ПЕРСПЕКТИВЫ РАЗВИТИЯ - Kalymbek, B. (Journal of actual problems of jurisprudence, 2019)
In this article establishment and development of Kazakhstan legislation in the field of veterinary safety and suggest ways of further improving.